Strategi Pegadaian Syariah Dalam Mendorong Ketahanan Ekonomi Melalui Prinsip Syariah - Rosita, Dita Puspa; B, Baidhowi (Media Hukum Indonesia (MHI), 2025)
Sharia Pawnshop plays a strategic role in strengthening national economic resilience by providing fair, transparent, and interest-free Sharia-based financing access. Through rahn and ijarah contracts, it helps communities, especially SMEs, obtain capital without the burden of interest, thereby supporting sustainable economic growth. Digitalization of services further expands financial inclusion and facilitates public access to Sharia-compliant financing. The findings show that Sharia Pawnshop serves as a crucial instrument in building an economy based on Islamic values, emphasizing justice, welfare, and blessings in financial transactions.